Plasma procalcitonin may be an early predictor of liver injury in acetaminophen poisoning: A prospective cohort study. Issue 5 (28th June 2021) - Nuzzo, Alexandre; Salem, Shireen; Malissin, Isabelle; Diallo, Abdourahmane; Deye, Nicolas; Goury, Antoine; Gourlain, Hervé; Péron, Nicolas; Vicaut, Eric; Voicu, Sebastian; Mégarbane, Bruno
Abstract: Background and Aims: Acetaminophen is a common cause of poisoning and liver injury worldwide; however, patient stratification is suboptimal. We aimed to assess the contribution of admission plasma procalcitonin concentration (PCT) to better identify acetaminophen‐poisoned patients likely to develop liver injury. Methods: We conducted a prospective observational cohort study including all acetaminophen‐poisoned patients requiring N‐acetylcysteine admitted in a toxicological intensive care unit between 2012 and 2017. Multivariate analysis was performed using a Cox regression model to investigate factors associated with liver injury, defined as an increase in alanine aminotransferase (ALT) >100 IU/L. Results: One hundred seventeen patients (age, 32 years (21–53), median [25th–75th percentiles]) were included after self‐ingesting 16 g (9–30) acetaminophen and received N‐acetylcysteine infusion administered within a median 6 h‐delay (4–12) from exposure. Co‐ingestions were reported in 77% of patients. Rumack–Matthew nomogram was non‐interpretable in 47% cases. Liver injury occurred in 38 patients (32%) with a median peak ALT of 2020 IU/L (577–4248). In liver injury patients, admission PCT was significantly increased in comparison to patients without liver injury (21.5 ng/ml (3.2–44.9) versus 0.1 ng/ml (0–0.4), respectively, p  < 0.01). The increase in PCT preceded the increase in ALT by 33 h (10–74). In a multivariate analysis, PCT > 1 ng/ml was significantly associated with liver injury (hazard ratio, 7.2 [95% confidence interval, 2.3–22.6; p  < 0.001]). PCT (area under the receiver‐operating characteristics curve, 0.91 [95%CI: 0.84–0.97]) predicted liver injury with sensitivity, specificity, negative, and positive predictive values of 0.92, 0.84, 0.96, and 0.73, respectively. Conclusion: PCT on admission is associated with liver injury in acetaminophen poisoning. PCT might be used as a predictive tool of liver injury to improve clinical decision‐making. Abstract :